Chordoid meningioma: Report of 5 cases and review of the literature - Tahta, Alican; Genç, Berkhan; Çakır, Aslı; Şekerci, Zeki (Taylor & Francis Ltd, 2023)
Chordoid meningioma is a rare, more aggressive subtype of meningioma. This study documents the histological, radiological and clinical features of seven tumours in five patients among 131 meningioma patients who were treated in the Department of Neurosurgery at Istanbul Medipol University between 2014 and 2019. There were two males and three females. All tumours were supratentorial. Surgical Simpson grade II resection was achieved in two cases, grade I in one and grade IV in two. One case relapsed and underwent further surgeries and adjuvant treatment. The chances of survival without recurrence after the Simpson grade I-II resection are high but close follow-up is recommended particularly if grade I cannot be achieved.
Keywords: Chordoid Meningioma; Surgery; Radiosurgery; Gamma-Knife; Recurrence